Stimulation of the calcium-sensing receptor stabilizes the podocyte cytoskeleton, improves cell survival, and reduces toxin-induced glomerulosclerosis - Oh, Jun; Schröder, Julia Cornelia; Bloch, Jacek; Hettgen, Verena; Müller, Julian; Li, Li; Hoemme, Meike; Groß-Weissmann, Marie-Luise; Penzel, Roland; Mundel, Peter; Schaefer, Franz; Schmitt, Claus P. (Kidney international, 2011)
Calcimimetics increase the sensitivity of the parathyroid calcium-sensing receptor to extracellular calcium for efficient control of hyperparathyroidism. Recent studies suggest that there are beneficial effects of calcimimetics beyond the control of bone and mineral homeostasis. Here, we tested whether the calcium-sensing receptor is also expressed and functionally relevant in podocytes. Analysis of microarray data using Gene Set Enrichment Analysis found that the calcimimetic R-568 influenced various pathways related to oxidative stress, cytoskeletal regulation, cell proliferation, and survival in cultured podocytes. R-568 induced a dose- and time-dependent phosphorylation of the ERK1/2-P90RSK-CREB signaling cascade, and induced pro-survival phosphorylation of BAD and Bcl-xl, thus reducing puromycin aminonucleoside (PAN)-induced podocyte apoptosis by half. Moreover, R-568 preserved the actin cytoskeleton in podocytes exposed to PAN and improved recovery from exposure to cytochalasin D, a reversible inhibitor of actin polymerization. In rats, co-administration of R-568 prevented the proteinuria caused by a single dose of PAN and attenuated the glomerulosclerosis and loss of GFR caused by repetitive puromycin treatment. Hence, calcimimetics limit podocyte damage by antiapoptotic and cytoskeleton-stabilizing effects and may constitute a new approach in the prevention and treatment of glomerular disease.